Process Simulation of Low-Carbon Cement Production Using Wollastonite as a Limestone Substitute - Sony Nugraha; Anton Irawan; Iqbal Syaichurrozi (World Chemical Engineering Journal, 2026)
The conventional limestone-based cement production process is widely recognized as one of the largest contributors to global carbon dioxide emissions. Carbon dioxide emissions are produced because of the calcination process of limestone, namely calcium carbonate, and high energy consumption. In the conventional cement manufacturing process, various efforts have been made to reduce the amount of carbon dioxide emissions produced, but these efforts have not yet reduced the amount of carbon dioxide emissions massively. A breakthrough step was made by using alternative raw materials, namely using silica rock to replace limestone, so that carbon dioxide emissions from the calcination process are not produced. This alternative production using silica rock uses a chemical approach where the process goes through the stages of leaching, separation, precipitation, dehydration, decomposition and clinkerization. Simulations focused on the leaching, separation and precipitation stages to predict the mass balance, solvent requirements and distribution of calcium and silica. The simulation results showed that the leaching stage conversion reached 99% at a temperature of 80oC and a retention time of 5 hours, while the precipitation stage conversion reached 99% at a temperature of 80oC and a retention time of 4 hours. Meanwhile, the potential reduction in carbon dioxide emissions reaches 70% because of the elimination of the calcination process, and the potential reduction in energy consumption in the rotary kiln unit reaches 60%. This study also provides an initial quantitative basis for developing a carbon-free cement production process.